Mechanically Strong and Multifunctional Polyimide Nanocomposites Using Amimophenyl Functionalized Graphene Nanosheets - Park, Ok-Kyung; Hwang, Jun-Yeon; Goh, Munju; Lee, Joong Hee; Ku, Bon-Cheol; You, Nam-Ho (AMER CHEMICAL SOC, 2013)
We report an effective way to fabricate mechanically strong and multifunctional polyimide (PI) nanocomposites using aminophenyl functionalized graphene nanosheet (APGNS). APGNS was successfully obtained through a diazonium salt reaction. PI composites with different loading of APGNS were prepared by in situ polymerization. Both the mechanical and electrical properties of the APGNS/PI composites were significantly improved compared with those of pure PI due to the homogeneous dispersion of APGNS and the strong interfacial covalent bonds between APGNS and the PI matrix. The electrical conductivity of APGNS/PI (3:97 w/w) was 6.6 x 10(-2) S/m which was about 10(11) times higher than that of pure PI. Furthermore, the modulus of APGNS/PI was increased up to 16.5 GPa, which is approximately a 610% enhancement compared to that of pure PI, and tensile strength was increased from 75 to 138 MPa. The water vapor transmission rate of APGNS/PI composites (3:97 w/w) was reduced by about 74% compared to that of pure PI.
Keywords: THERMAL-PROPERTIES; CARBON NANOTUBES; OXIDE; REDUCTION; SHEETS; RAMAN; FILM